Can the wrf model characterize atmospheric stability for wind energy purposes? - Mayol, María Laura (2023)
To foster energy transition, renewable energies need to achieve their full potential. One phenomena greatly impacting power production in wind energy is the wake production behind each wind turbine or entire farms. These wake regions are strongly modulated by low-layer atmospheric stability. In this work, the capability of the WRF mesoscale model to characterize the stability in the Rawson Wind Farm location is addressed. Through a dynamical downscaling from ERA5 data, the WRF outcomes are used to estimate the stability parameter RiB, which is compared to the one computed from measurements. A great similarity emerges from the analysis, in statistical terms, between the stability conditions estimated from the observations and those resulting from the simulations. These results encourage the use of mesoscale models to obtain a more detailed description of the low-layer flow and therefore reduce the uncertainties linked to the environmental conditions that affect a wind farm.